Utilization of magnetic sugarcane baggase for methylene blue dye removal from water: equilibrium and kinetic studies / Nurul Izza Husin, Hami Hakimah Azmi and Nurafiqah Zawawi - Husin, Nurul Izza; Azmi, Hami Hakimah; Zawawi, Nurafiqah (Universiti Teknologi MARA Cawangan Pulau Pinang, 2018)
Dyes enforces ecological and public problems due to hazardous and irretrievable properties of such pollutants on human health and the environment. Therefore, it is vital to treat this pollutant efficiently and effectively. In this study Magnetic Sugarcane Bagasse (SGB) was prepared as an alternative biosorbent for Methylene Blue (MB) dye removal from water. The Magnetic SGB characterization was performed using Fourier Transform Infrared Spectroscopy. Batch adsorption study was investigated with respect to its adsorption equilibrium, isotherm, and kinetics. The equilibrium was achieved within 75 minutes with maximum removal efficiency around 94.75%. For isotherm study, Langmuir isotherm is well fitted compared to the Freundlich isotherm. Therefore, it demonstrates that the process involved is monolayer adsorption on a homogeneous surface. In addition, the kinetic study shows that the adsorption process has the best agreement with pseudo-second-order kinetic models which describes that the process may involve chemisorption. The results show that Magnetic SGB could be used as low-cost alternative adsorbent for the removal of MB.